Eksplorasi Implementasi Prinsip Character, Capacity, Capital, Collateral, dan Condition Dalam Pembiayaan Murabahah di BPRS Bhakti Sumekar Sumenep - Muhammad Rifai Bin Mohd Umar; Ilham Abdul Jalil (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
The rapid development of the Islamic finance industry does not mean that it does not experience several problems, including financing with murabahah contracts which contain many complex and diverse risks. Risk management is an effort to optimize profits in the Islamic financial industry business and minimize the risk of default for customers. The researcher is interested in researching the application of the 5C principle in murabahah financing at BPRS Bhakti Sumekar Sumenep which aims to find out how the implementation of the 5C principle in murabahah financing at BPRS Bhakti Sumekar Sumenep and what are the factors that cause problematic murabahah financing at BPRS Bhakti Sumekar Sumenep. The research method used by the researcher is descriptive qualitative research with data sourced from primary and secondary data, as well as data collection techniques used in the form of observation, interviews and documentation, while data analysis techniques used are in the form of data reduction, data presentation and conclusion drawing. The application of the 5C principle in murabahah financing at BPRS Bhakti Sumekar Sumenep assesses the seriousness and integrity of the debtor, measures the debtor's business activities and income, measures the amount of capital ownership in business activities, calculates the collateral owned by the customer and looks at and assesses the condition or circumstances of the customer, while the factors that cause problematic murabahah financing at BPRS Bhakti Sumekar Sumenep are in the form of unstable economic conditions, the physical condition of the customer and the factors of business activities are not supportive.